International Marketing Strategy / Analysis, Development and Implementation - Doole Isobel; Lowe Robin (Cengage Learning Emea, 2008)
A perspective, practical and up-to-date look into the ever-changing world of international marketing. Analysis, An Introduction to International Marketing, The International Trading Environment, Social and Cultural Considerations in International Marketing, International Marketing Research and Opportunity Analysis, Strategy Development, International Niche Marketing Strategies for Small and Medium-Sized Enterprises, Global Strategies, Market Entry Strategies, International Product and Service Management, Implementation, International Communications, The Management of International Distribution and Logistics, Pricing for International Markets, International Marketing Implementation through Enabling Technologies.